Chiral Bioinspired Plasmonics: A Paradigm Shift for Optical Activity and Photochemistry - Óscar Ávalos‐Ovando; Eva Yazmin Santiago; Artur Movsesyan; Xiang‐Tian Kong; Peng Yu; Lucas V. Besteiro; Larousse Khosravi Khorashad; Hiromi Okamoto; Joseph M. Slocik; Miguel A. Correa‐Duarte; Miguel Comesaña‐Hermo; Tim Liedl; et al. (2022)
This Perspective concerns the latest developments in the field of chiral nanocrystals (NCs) and metastructures, focusing primarily on plasmonic nanostructures. Such nanomaterials exhibit unusually strong near-field and electromagnetic responses that enable efficient biosensing and light manipulation. Herein we share our thoughts on the latest trends that mark what we call a paradigm shift for the vast and dynamic field of chiroptical materials. The topics to be considered include polarization-sensitive photocatalysis with chiral plasmonic NCs, chiral bioconjugates, DNA-based assemblies, chiral growth, and we also describe the fundamental challenges for optical induction of chirality, transfer of chirality between different scales, and theoretical issues that nanoscience is facing.